2019
DOI: 10.3390/molecules24224115
|View full text |Cite
|
Sign up to set email alerts
|

5,8-Quinolinedione Scaffold as a Promising Moiety of Bioactive Agents

Abstract: Natural 5,8-quinolinedione antibiotics exhibit a broad spectrum of activities including anticancer, antibacterial, antifungal, and antimalarial activities. The structure–activity research showed that the 5,8-quinolinedione scaffold is responsible for its biological effect. The subject of this review report is a presentation of the pharmacological activity of synthetic 5,8-quinolinedione compounds containing different groups at C-6 and/or C-7 positions. The relationship between the activity and the mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 100 publications
0
11
0
Order By: Relevance
“…The Streptomyces species produce compounds containing the 5,8-quinolinedione moiety, such as streptonigrin , lavendamycin , and streptonigron , which exhibit a wide spectrum of biological activity ( Figure 1 ) [ 8 , 9 ]. Previous studies dealt with the modification of 5,8-quinolinedione moiety at the C-2, C-6, and C-7 positions and they showed that such modification can lead to changes in biological activity [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Streptomyces species produce compounds containing the 5,8-quinolinedione moiety, such as streptonigrin , lavendamycin , and streptonigron , which exhibit a wide spectrum of biological activity ( Figure 1 ) [ 8 , 9 ]. Previous studies dealt with the modification of 5,8-quinolinedione moiety at the C-2, C-6, and C-7 positions and they showed that such modification can lead to changes in biological activity [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tested compounds contain two active moieties, i.e., 1,4-quinone and betulin. The main mechanism of activity for 1,4-quinone derivatives is the interaction with NQO1 protein, for which the overexpression is observed in many types of cancer cell lines [ 8 , 10 , 24 ]. The betulin derivatives show a wide spectrum of activities including anticancer, antiviral, antibacterial, and anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to their toxicity, only a few compounds were evaluated in clinical trials. Attempts to design and synthesize analogues endowed with lower toxicity are currently being performed [ 25 ].…”
Section: Naphthoquinone and Quinolinedione Scaffolds In Antitumor Hyb...mentioning
confidence: 99%
“…The alkaloid streptonigrin isolated from Streptomyces displaying anti-leukemic properties, and the ascidian metabolites ascidiathiazones A and B are examples of molecules belonging to this class. This moiety is considered promising in the synthesis of bioactive agents [ 25 ]. However, to date few studies have been reported considering this scaffold in the synthesis of anticancer hybrids.…”
Section: Design Synthesis and Biological Evaluation Of Antitumor Hybridsmentioning
confidence: 99%
“…For example, natural, such as streptonigrin, and synthetic 5,8-quinolinedione compounds show wide spectrum of biological activities such as anticancer, antibacterial, and antiviral. The activity depends on the substituent at the positions C-6, C-7 and C-2 of the 5,8-quinolinedione moiety ( Figure 1 ) [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%